2022
DOI: 10.3390/s22208053
|View full text |Cite
|
Sign up to set email alerts
|

Farmers and Local Residents Collaborate: Application of a Participatory Citizen Science Approach to Characterising Air Quality in a Rural Area in The Netherlands

Abstract: In rural areas, livestock farming is a source of environmental concern. We describe a citizen science (CS) project in Venray, the Netherlands, where air quality was measured at livestock farms and surrounding residential premises. We used low-cost methods to measure air quality components and facilitated a dialogue between stakeholders about the results and solutions for cleaner air. PM2.5 and PM10 were measured using Nova Fitness SDS011 sensors, nitrogen dioxide (NO2) and ammonia (NH3) using Palmes tubes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 36 publications
0
0
1
Order By: Relevance
“…Daily median values above 70% relative humidity happened for 219 days, 39.4% of the total. We found that relative humidity had no clear effect on the data for our site (see Figure 7 ), in contrast with other authors who found that relative humidity above 80% [ 33 ] or 95% [ 34 ] negatively affected the SDS011 sensor response. In our dataset, values above the 80 and 95% relative humidity thresholds were found in 17.3% and 0.2% of the analyzed days, respectively.…”
Section: Resultscontrasting
confidence: 99%
“…Daily median values above 70% relative humidity happened for 219 days, 39.4% of the total. We found that relative humidity had no clear effect on the data for our site (see Figure 7 ), in contrast with other authors who found that relative humidity above 80% [ 33 ] or 95% [ 34 ] negatively affected the SDS011 sensor response. In our dataset, values above the 80 and 95% relative humidity thresholds were found in 17.3% and 0.2% of the analyzed days, respectively.…”
Section: Resultscontrasting
confidence: 99%